2003
DOI: 10.2304/eerj.2003.2.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Students' Concepts of Democracy

Abstract: In addition to assessing the civic knowledge and skills of adolescents, examining students' concepts of democracy was an important aspect of the International Association for the Evaluation of Educational Achievement (IEA) Civic Education Study. Based on theories and previous research with adults and youth in this area, a set of survey items was developed to cover several models of democracy. In the 1999 IEA Civic Education Study of 14 year olds, the confirmatory factor analysis showed one factor with items re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 5 publications
2
18
0
2
Order By: Relevance
“…Many adolescents are not able to define democracy or provide a coherent description of it. Those who are able to define democracy, moreover, typically do so in terms of such characteristics as individual rights and freedoms, democratic representation, majority rule, and/or civic equality (Husfeldt and Nikolova 2003;Flanagan 2013;Flanagan et al 2005). Only a small group of adolescents have been shown to be able to provide a more comprehensive account of the concept of democracy by mentioning several key characteristics, relating these to each other and explaining why they constitute a democracy (De Groot 2013;Sigel and Hoskins 1981).…”
Section: Orientations Towards Democracy and Decision-makingmentioning
confidence: 99%
“…Many adolescents are not able to define democracy or provide a coherent description of it. Those who are able to define democracy, moreover, typically do so in terms of such characteristics as individual rights and freedoms, democratic representation, majority rule, and/or civic equality (Husfeldt and Nikolova 2003;Flanagan 2013;Flanagan et al 2005). Only a small group of adolescents have been shown to be able to provide a more comprehensive account of the concept of democracy by mentioning several key characteristics, relating these to each other and explaining why they constitute a democracy (De Groot 2013;Sigel and Hoskins 1981).…”
Section: Orientations Towards Democracy and Decision-makingmentioning
confidence: 99%
“…Political socialization research shows two developments in how adolescents gain a fuller perspective on the political world: increasing familiarity with politics and increasing complexity in reasoning about democratic issues. As to the first development, it is suggested that adolescents grow into politics by becoming more familiar with abstract institutions and principles, such as government, parliament, and the concept of democracy (Greenstein, 1965;Hooghe and Dassonneville, 2011;Husfeldt and Nikolova, 2003;Sapiro, 2004). While children develop views and attitudes towards aspects of everyday situations such as choice of friends, bullying, and boundaries of parental control over the preferences of their children (Helwig and Turiel, 2002), adolescents usually also develop democratic orientations (Adelson, 1971;Husfeldt and Nikolova, 2003).…”
Section: Developing Democratic Views During Adolescencementioning
confidence: 99%
“…These scales were included in the discriminant function analysis because these values and attitudes are among important civic learning outcomes for active citizenship reported in the literature, such as democratic values (Papanastasiou, Koutselini, & Papanastasiou, 2003), civic concepts (Husfeldt & Nikolova, 2003;Kontogiannopoulou-Polydorides, Fragoulis, Zanni, & Ntelikou, 2003), civic engagement and participation (Menezes, 2003;Torney-Purta & Richardson, 2002), democratic school engagement and civic participation 482…”
Section: External Validitymentioning
confidence: 99%